Ladder-based resistance training with the progression of training load altered the tibial nerve ultrastructure and muscle fiber area without altering the morphology of the postsynaptic compartment - Krause Neto, Walter; Silva, Wellington; Oliveira, Tony; Vilas Boas, Alan; Ciena, Adriano; Caperuto, Érico Chagas; Gama, Eliane Florencio (Frontiers in Physiology, 2024)
Scientific evidence regarding the effect of different ladder-based resistance training (LRT) protocols on the morphology of the neuromuscular system is scarce. Therefore, the present study aimed to compare the morphological response induced by different LRT protocols in the ultrastructure of the tibial nerve and morphology of the motor endplate and muscle fibers of the soleus and plantaris muscles of young adult Wistar rats. Rats were divided into groups: sedentary control (CONTROL, n=9), a predetermined number of climbs and progressive submaximal intensity (FIXED, n=9), high-intensity and highvolume pyramidal system with a predetermined number of climbs (PYRAMID, n = 9) and LRT with a high-intensity pyramidal system to exhaustion (FAILURE, n = 9). Myelinated fibers and myelin sheath thickness were statistically larger in PYRAMID, FIXED, and FAILURE. Myelinated axons were statistically larger in PYRAMID than in CONTROL. Schwann cell nuclei were statistically larger in PYRAMID, FIXED, and FAILURE. Microtubules and neurofilaments were greater in PYRAMID than in CONTROL. Morphological analysis of the postsynaptic component of the plantar and soleus muscles did not indicate any significant difference. For plantaris, the type I myofibers were statistically larger in the PYRAMID and FIXED compared to CONTROL. The PYRAMID, FIXED, and FAILURE groups for type II myofibers had larger CSA than CONTROL. For soleus, the type I myofibers were statistically larger in the PYRAMID than in CONTROL. PYRAMID and FIXED had larger CSA for type II myofibers than CONTROL and FAILURE. The PYRAMID and FIXED groups showed greater mass progression delta than the FAILURE. We concluded that the LRT protocols with greater volume and progression of accumulated mass elicit more significant changes in the ultrastructure of the tibial nerve and muscle hypertrophy without endplate changes.